Music and Singing in The Heritage of Baghdadi The 1930s is a Model (Journal of the College of Education for Women, 2019)
Music and singing are always associated with the movement of society and the emergence of cultural and artistic activities other.The social and political transformations of the 1930s helped to disseminate the study Music and music in the city of Baghdad and across Iraq This is the beginning of a new era of musical art alongside other arts.While achieving musical arts A new step was advanced by publishing a technical study among the younger generation they were looking for to contribute to the musical field On the other hand, the city of Baghdad during the period of research many musical and musical performances Egyptian teams have provided many artistic activities and events which have had a significant impact on the development the musical arts and the general art movement in Baghdad and the rest of Iraq.